Innovation waste management: Creating probiotic tepache business for the community of Kebonduren Village - Ratna Juwita; Danda Ash Shaka Habibullah; Eriko Mandala Haji Pitra; Shandy Bagas Syahputra; Candra Kurniawan Ramadhani; Algafari Bakti Manggara (Community Empowerment, 2025)
Kebonduren Village has high pineapple production potential, but also produces increasing and unmanaged pineapple peel waste which has the potential to harm the community. One solution is to turn pineapple peel into a tepache probiotic drink, a Mexican drink that is fermented for 3-5 days. Tepache is useful for improving digestion and endurance thanks to its lactic acid bacteria content. The purpose of this community service is to create business opportunities for mothers of the Family Empowerment and Welfare (PKK) in Kebonduren Village. The methods applied include preparation, training, mentoring, and evaluation, with all participants filling out questionnaires before and after the training. The results of the training showed significant improvements; all participants not only understood the content of pineapple peel but were also able to make tepache probiotic drinks and knew their benefits. Before the training, 100% of participants had never made tepache, but after the training, 100% of participants succeeded in producing it. This shows the effectiveness of the training in improving the understanding and skills of PKK mothers, which is very important for the success of the community service program.